6 - An Analysis of the Impact of ICT Investment on Productivity in Developing Countries: Evidence from Cameroon - Nkama, Arsene Honore Gideon (Africa Development, 2021)
To what extent have investments in Information and Communication Technologies (ICT) contributed to productivity growth in Cameroon? This paper explores the relationship between productivity and investment in ICT in Cameroon at the level of firms in 2004. Using cross- sectional data and applying a Cobb-Douglas function, the study reveals that investment in ICT has no impact on productivity, as the estimated coefficient of ICT investment on productivity is not significant. Also, ICT investment has no impact on labour productivity and labour intensity. These findings differ from Chowdhury and Wolf (2002) who found that ICT investment has a negative and significant impact on labour productivity in East Africa. In Cameroon labour remains the key factor of value added growth. This seems to be realistic as the country has a growing workforce that tends to slow down salaries. Since labour is the abundant factor, it is profitable for firms to increase their production by recruiting additional units of labour. If ICT investment contributes to rapid globalization of economies, it does not yet contribute to productivity growth in Cameroon.